ANALISIS STRUKTUR BIAYA DAN KINERJA OPERASIONAL BANK UMUM DI INDONESIA - Siswadi, Erwinta; Arafat, Wilson (Journal of Indonesian Economy and Business, 2004)
The âturbulenceâ that becomes a characteristic in business environment now hasleaded the business to the very tight competition (known as hypercompetition), and it also influenced banking industry.With that situation, efficient and effective at cost structure and operational performancewill determine the bank performance either survive or not. For that reason, the study willbe conducted to analyze the cost structure and bank performance in Indonesia using twoapproaches: (1) Parametric approach based on translog cost function framework toanalyze cost structure in banking industry in Indonesia; (2) Non-Parametric approachbased on linear programming framework to evaluate the operational performance inIndonesian banking that shown by efficiency index.The study used data from 50 banks that have the biggest assets in Indonesia during1998-2002 periods. According to the analysis, it showed âthe red lineâ that strictly stated:(1) Using parametric approach, it showed that cost structure in Indonesian banking hasfulfilled translog cost function. Indonesian banking industry is now facing âscale ofeconomiesâ and âscope of economiesâ conditions. The research has shown that banks with the bigger assets showed higher level of scale of economies. (2) Based on non-parametric approach, it indicated that banking in Indonesia could reduce their operational cost up to 89,40% comparing with their present operational cost. Cost inefficiency mainly caused by inappropriate technical efficiency that can be eliminated if only banking industry in Indonesia have used input components optimally.Keywords: Cost Structure, Operational Performance, Parametric Approach, Non-Parametric Approach.